Evaluation of the Compactness of Benefit Coupling of Farmers' Cooperatives in Poor Areas: Based on the Date in Qinba and Wumeng Areas in Sichuan, China. Issue 4 (March 2020) - Fu, Xinhong; Du, Zhijing; Zhang, Xiyu; Chen, Xue; Li, Jianqiang
Abstract: As a new type of agricultural management, farmers' cooperatives play a critical role in the development of rural industries and the promotion of farmers' poverty alleviation. However, in recent years, the problem of non-standardization and "empty shelling" of farmers' cooperatives has seriously restricted the common development of their interests with members. Based on the field research of farmers' cooperatives in the poverty-stricken areas of Qinba and Wumeng in Sichuan, this paper estimates the close relationship of the interests of farmers' cooperatives in poor areas in Sichuan and summarizes the problems of farmers' cooperatives in poor areas. The empirical results show that the poverty alleviation funds invested in the cooperatives have a positive effect on the compactness of benefit coupling, that the cooperatives are more closely related to the degree of closeness, and the sales linkage and rebate linkage are mainly semi-closed. The degree of frequency of the looseness of the equity linkage is high, and the tightness of service is mainly loose. Therefore, it is suggested that cooperatives should integrate resources, quantify equity, and clarify property rights to strengthen the close connection with the interests of members, and drive farmers to lift poverty and increase income.